Knowledge, attitude and practice regarding exercise among people exercising in gymnasium and recreational parks around Kuantan, Malaysia - Nor Iza, A.Rahman; Mohamed Afif Asyraf, Mohamed Roshdin Murad; Nor Azlina, A. Rahman (Open Science Publishers LLP Inc., 2016)
Physical inactivity is becoming a global epidemic and lead to many diseases. This cross-sectional study tried to investigate knowledge, attitude and practice (KAP) regarding exercise among married and single person attending gymnasium and recreational parks. Furthermore, this study tried to look for factors associated with regularity of exercise and to find association between knowledge and attitude on practice of exercise. A total of 103 participants aged above 18 years old were purposely selected to answer an interview-guided questionnaire. Likert scale was used for participants to answer the questionnaire on KAP and the total score for each knowledge, attitude and practice was computed to find the associations using SPSS. The mean age of the respondent was 25.34 years (SD=5.699). Knowledge was not significantly associated with practice (r=0.071, p=0.475). There was also no significant correlation between practice and attitude score (r=0.006, p=0.510). Therefore, there is no association between knowledge and attitude on practice of exercise. Besides that, endurance exercise like jogging, cycling and walking was a respondent's choice as their exercise routine. Other than that, there are significant associations between factors of gender (p=0.014), marital status (p<0.001) and age (p=0.005) with regularity of exercise. This study found that single person is more regularly doing exercise than married people. Regularity of exercise could be influenced by motivation. Therefore, relevant policies and campaigns might be able to change and boost people towards practicing exercise regularly in Malaysia.